Systematization of experiences: local organization and construction of citizenship, an approach to disability - Ramírez Morera, Marcela (2023)
Introduction: this article recovers the main results of the systematization of experiences carried out within the framework of the Workshop: Local Organization and Construction of Citizenship I and II, of the third year of the study plan of the Social Work career of the University of Costa Rica (UCR). Objective: to identify the various contributions of the academic experience in Social Work to the construction of citizenship and recognition, defense and enforceability of the rights of people with disabilities, during the period of 2021-2022. Method: this research is supported by the documentary review and the academic experience of the Workshop: Local Organization and Construction of Citizenship I and II, as well as the final report developed by the students in 2021-2022 Results: the third-year academic practice is a space for reflection and historical apprehension of reality in the local space for students. The systematization of experiences allows us to visualize the work with organizations, strategic lines of action, organizational processes and challenges at the community level. Conclusions: Social Work has a strong interference in local processes and construction of citizenship from its academic practices, which allows its students to develop skills. Academic internships are and will continue to be a privileged space for contact with populations and in Belén, an exceptional bridge for the development of an accessible and friendly locality, especially for all people with disabilities.